2009
DOI: 10.1180/minmag.2009.073.5.777
|View full text |Cite
|
Sign up to set email alerts
|

Compositional variation in the chevkinite group: new data from igneous and metamorphic rocks

Abstract: Electron microprobe analyses are presented of chevkinite-group minerals from Canada, USA, Guatemala, Norway, Scotland, Italy and India. The host rocks are metacarbonates, alkaline and subalkaline granitoids, quartz-bearing pegmatites, carbonatite and an inferred K-rich tuff. The analyses extend slightly the range of compositions in the chevkinite group, e.g. the most MgO-rich phases yet recorded, and we report two further examples where La is the dominant cation in the A site. Patchily- zoned crystals from Vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 43 publications
2
34
0
9
Order By: Relevance
“…Differentiation of metaluminous silicic magma and/or increasing peralkalinity typically results in crystallization of chevkinite with higher La, Ce, Mn, Fe, and Nb concentrations, and lower Al, Ti, Mg, Ca, and MREE concentrations (Macdonald et al, , 2009 Primavera and Yellowstone chevkinite follow this general trend and are consistent with increasing magnitude of differentiation and/or peralkalinity of their host rocks. West Yellowstone chevkinite has lower average Th/U, Mg/Fe, Fe and Th, and higher average Mn, Zr, and Nb with decreasing age (Fig.…”
Section: Age-compositional Relations Of La Primavera and Yellowstone supporting
confidence: 67%
See 2 more Smart Citations
“…Differentiation of metaluminous silicic magma and/or increasing peralkalinity typically results in crystallization of chevkinite with higher La, Ce, Mn, Fe, and Nb concentrations, and lower Al, Ti, Mg, Ca, and MREE concentrations (Macdonald et al, , 2009 Primavera and Yellowstone chevkinite follow this general trend and are consistent with increasing magnitude of differentiation and/or peralkalinity of their host rocks. West Yellowstone chevkinite has lower average Th/U, Mg/Fe, Fe and Th, and higher average Mn, Zr, and Nb with decreasing age (Fig.…”
Section: Age-compositional Relations Of La Primavera and Yellowstone supporting
confidence: 67%
“…Concentrations of light rare earth elements (LREEs) typically range between 9-25 wt.% (Ce, La) 2 O 3 (Macdonald et al, , 2009, giving chevkinite some of the highest observed crystal/melt partition coefficients for LREE Troll et al, 2003). Heavy rare earth element concentrations in chevkinite are typically 1-3 orders of magnitude lower than LREE .…”
Section: Compositions and Crystallization Of Chevkinite-(ce) In Silicmentioning
confidence: 98%
See 1 more Smart Citation
“…2b, are presented in Table 1, and supplemented in Supplementary Table 1a by five analyses from Macdonald et al (2012). The phase has been classified as chevkinite-(Ce) using the empirical discriminant of Macdonald et al (2009) (Fig. 7) Compositions of the altered chevkinite (Zone B) are given in Table 1 and Supplementary Table 1a.…”
Section: Mineral Compositionsmentioning
confidence: 99%
“…Fig. 7 Empirical discrimination plot of chevkinite and perrierite (Macdonald et al 2009). The unaltered chevkinite-(Ce) plots in the chevkinite field, whereas the altered chevkinite spreads into the perrierite field.…”
Section: Nb-bearing Phasesmentioning
confidence: 99%